2007
DOI: 10.1111/j.1743-6109.2006.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Vein Injuries Observed During Penile Exploration for Suspected Penile Fracture

Abstract: Introduction Penile fracture is a rare injury, bearing potential impairment of erectile function if not treated. Patients with clinical presentation of a penile fracture commonly undergo early surgical exploration with the intention to repair a tunica albuginea tear. Aim We present a group of men who presented with a penile hematoma following trauma to the erect penis. Exploration revealed an intact tunica albuginea and a dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
2
30
1
Order By: Relevance
“…Even though there are no large cohorts to provide data on dorsal penile vein rupture and the associated risk factors, BarYosef and colleagues have described their experience with 9 patients. 3 They suggested that circumcision could be one of the risk factors for dorsal vein rupture due to stretching of the penile skin during intercourse. Similarly, Baran and colleagues concluded that circumcision could have been the mechanism of injury in their patient with superficial penile dorsal vein rupture after surgical exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though there are no large cohorts to provide data on dorsal penile vein rupture and the associated risk factors, BarYosef and colleagues have described their experience with 9 patients. 3 They suggested that circumcision could be one of the risk factors for dorsal vein rupture due to stretching of the penile skin during intercourse. Similarly, Baran and colleagues concluded that circumcision could have been the mechanism of injury in their patient with superficial penile dorsal vein rupture after surgical exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with penile fracture would report hearing a "snap" sound, which is followed by pain, penile detumescence, and late appearing swelling, hematoma and penile deformity. 3,4 When there is associated urethral injury, we sometimes notice concurrent urethral bleeding, difficulty voiding and hematuria. 5 However, patients with rupture of the superficial dorsal vein of the penis may not describe the classic "snap-pop" or rapid detumescence.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Mydlo et al [ 1 ] found that the cavernosographic fi ndings were falsely negative in two of seven patients with penile fracture, suggesting a possible ball-valve effect of the underlying hematoma. BarYosef et al [ 12 ] reported the high incidence of dorsal vein injuries observed during penile exploration for suspected penile fracture. The results of that study showed that in 9 of 17 operations, the tunica albuginea was intact, and the only pathologic fi nding was a rupture of the dorsal vein [ 12 ].…”
Section: Diagnosismentioning
confidence: 98%
“…BarYosef et al [ 12 ] reported the high incidence of dorsal vein injuries observed during penile exploration for suspected penile fracture. The results of that study showed that in 9 of 17 operations, the tunica albuginea was intact, and the only pathologic fi nding was a rupture of the dorsal vein [ 12 ]. These results are important in regards to the use of additional techniques for the diagnosis of penile fracture.…”
Section: Diagnosismentioning
confidence: 98%
“…2 Many conditions can simulate fracture penis as dorsal vein tears in penis may mimic penile fracture. 3 …”
Section: Introductionmentioning
confidence: 99%